(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: The more medicine develops, the more surgical procedures are operated in the elderly, especially orthopedic surgeries of the lower limbs such as hip replacement, knee replacement. Spinal anesthesia has been linked to reduce risk of perioperative complications when compared with other methods. Purposes: To determine the effect of spinal anesthesia for hip replacement surgery and perioperative adverse events. Study methods: Case series. Results: The degree of motor and sensory block achieve a suitable condition for procedures (NRS<3, Bromage score 3) with about 95.5%. Hypotension is the most common adverse effect after spinal anesthesia accounting for 54.5%. Conclusion: Subarachnoid block has many benefits for hip surgery in the elderly, but we require the awareness of frequent adverse effects, principally hypotension and bradycardia after spinal anesthesia.